Isothermal Crystallization Properties of Rbd-Palm Oil as Measured By Dsc and Oscillatory Rheometry - Bangun P. Nusantoro (agriTECH, 2009)
In this research, the crystallization properties of refined bleached and deodorized (RBD) palm oil under isothermal conditions were investigated. A good quality of RBD palm oil (showed by IV, FFA content, PV, and AV with the values of 52.14, 0.06%, 1.39 meq/kg, and 0.88, respectively) was used in this research. In general, RBD palm oil demonstrat ed a twostep crystallization process at the isothermal crystallization temperatures/  of 18oC, 20oC and 22oC. From differential scanning calorimetry (DSC) measurement of RBD palm oil, the melting heats/showed decrement values (33.84 J/g, 26.83 J/g and 22.47 J/g) but the peaks of the corresponding endotherm/ showed increment values (33.52oC, 34.72oC and 36.44oC) when both were correlated to the increased values of iso thermal crystallization temperatures/  (18oC, 20oC, and 22oC, respectively). From rheometry analysis of RBD palm oil (at the isothermal crystallization temperature of 18oC), the rheograms gave the values of the phase shift angle ( ), storage modulus () and complex modulus () at the end of crystallization process as follows: 24o,11.36 kPa, and 39 kPa. The overlay of   andgavewith the value of 49.6 Pa at the isothermal time of 11.7 minute.